Learning object-oriented programming : explore and crack the OOP code in Python, JavaScript, and C# - Hillar, Gaston C. (Birmingham, UK : Packt Publishing, Limited, 2015)
Object-oriented programming, also known as OOP, is a required skill in absolutely any modern software developer job. It makes a lot of sense because object-oriented programming allows you to maximize code reuse and minimize the maintenance costs. However, learning object-oriented programming is challenging because it includes too many abstract concepts that require real-life examples to make it easy to understand. In addition, object-oriented code that doesn't follow best practices can easily become a maintenance nightmare.
Chapter 1. Objects everywhere -- Chapter 2. Classes and instances -- Chapter 3. Encapsulation of data -- Chapter 4. Inheritance and specialization -- Chapter 5. Interfaces, multiple inheritance, and composition -- Chapter 6. Duck typing and generics -- Chapter 7. Organization of object-oriented code -- Chapter 8. taking full advantage of object- oriented programming.
Includes index.
Keywords: C# -- COMPUTER PROGRAMMING LANGUAGE